Achievement Profiles in Math, Science, and English: Exploring Contextualized Sex Differences - Española, Raymon Pomoy (Jurnal Pendidikan Progresif, 2023)
Achievement Profiles in Math, Science, and English: Exploring Contextualized Sex Differences. Objectives: The study used a person-oriented approach to explore sex differences at the level of achievement profiles and describe such differences in the context of urban/rural schools. Methods: The achievement test scores in math, science and English of 2,408 tenth graders sampled from the database of the Center for Educational Measurement (CEM) in the Philippines  were used to derive achievement profiles through cluster analysis. Findings: Four profiles were derived: 1) Low Achievers, 2) True Average Achievers, 3) High Achievers with weak math and science skills, and 4) High Achievers with strong math and science skills. Significant sex and urban/rural school differences among the profiles were found. The “female advantage” was more evident among Low Achievers, but not among High Achievers. When the urban/rural school context was considered, the female advantage tended to disappear and the urban school advantage became more apparent. Finally, High Achievers with weak math and science skills were mostly females in urban schools. Conclusion: The findings suggest that it was important to situate sex differences in context in order to understand achievement in key courses, such as STEM, of young children. Keywords: sex differences, urban and rural schools, achievement profiles, cluster analysis, FilipinoDOI: http://dx.doi.org/10.23960/jpp.v13.i1.202308